A facile one-step method to reduce surface impurities in solution-processed CuInS2 nanocrystal solar cells. Issue 27 (19th June 2015) - Stahl, Melissa S.; Azimi, Hamed; Brabec, Christoph J.
Abstract : This work presents a simple method for post-processing of washing away the impurities formed on the films of solution processed CuInS2 thin films. Abstract : The presence of impurities and disorders presents a potential barrier for the success of solution processed inorganic nanocrystalline devices. The removal of impurities typically requires harsh conditions and complex procedures that limit utility. This paper demonstrates the successful use of a set of solvents, which can efficaciously remove the surface impurities formed during in situ deposition of CuInS2 nanocrystals. These impurities include a hard-to-remove byproduct melamine that is formed by the decomposition of thiourea at elevated temperatures, and other organic residues like amines, conjugated organic systems, as well as ketones, aldehydes or esters. This work provides some design rules for the selection of solvents for removal purposes that could potentially be used for other absorber materials as well.